(untitled) (Revista de Ciências Agroveterinárias, 2015)
Yellow sigatoka (Mycosphaerella musicola) is the main disease in banana areas in the Santa Catarina state. The objective of this research was to evaluate the effect of different methods of chemical and cultural control of sigatoka disease on Prata banana in subtropical climate. Six treatments were tested, evaluating three formulations (Tebuconazole 0,5 L ha-1 - Tiofanato metílico 0,6 L ha-1; Citric biomass 1,0 L ha-1; water) with or without leaf removal. The variables evaluated were under the curve of progress (AUDPC) and final gross sum (GSfinal) area. The experimental design was randomized blocks in factorial scheme with five repetitions. Treatments were compared with Duncan´s test (P<0,05). Significant differences were verified for products compared to control, but not for leaf removal. It was found that fungicides and citric biomass resulted in significant reductions in AUDPC and GS final when compared to control. Fungicides and citric biomass reduced area under disease progress curve by 65 and 63%, as well as final gross sum were 87 and 73%, respectively. Results showed small influence of leaf removal, but new studies should evaluate its influence with higher frequency of defoliation. Fungicides and citric biomass are efficient in controlling sigatoka.